Z teorii płyt ortotropowych - BOGUSZ, Władysław (Engineering Transactions, 1954)
From the theory of orthotropic plates The paper brings a transformation reducing the quasi-biharmonic equation of the surface of deflection of an orthotropic plate to two partial differential equations of the second order, one of which is harmonic. Such a way of expressing the equation of the surface of deflection of an orthotropic plate permits the use of the two-stage method as used for isotropic plates, and which consists in a successive solution of two partial differential equations of the second order instead of one equation of the fourth order.